ETHNOBOTANY KNOWLEDGE OF PUBLIC SCHOOL STUDENTS IN THE CITY OF POMBAL-PB - Soares Sousa, Luci Cleide Farias; Silva Sousa, Jessenildo Elson da; Silva Sousa, José da; Wanderley, José Alberto Calado; Borges, Maria da Glória Borba (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2011)
In order to know the use and the plants used as medicine, a survey was conducted with students’ from9 year of the Municipal School of Elementary Education "Decisão" in the municipality of Pombal PB, in August 2011, where were applied 27 questionnaires with 27 students. Interviews applied in form of questionnaires, they resulted in the identification of 27 species distributed in 19 families, being that the families Lamiaceae, followed by Fabaceae and Anacardiaceae were those that had a greater representation. The plant most often cited in interviews was mint (Plectranthus amboinicus) (Lour.) Spreng, followed by lemongrass (Cymbopogon citratus) (DC.) Stapf. and Malva (Plectranthus barbatus) (Andr.) Benth. The most used parts of the plant were root with more representation, followed by bark, fruits and flowers. The main form of preparation is tea followed by juice and syrup. With regard to the purpose of homemade preparations showed a greater use in cases of flu, inflammation, headache, kidney pain, fever, diarrhea and pain of urine.